Identifikasi Endoparasit Tikus yang Berpotensi Zoonosis di Tiga Desa Kabupaten Bogor Jawa Barat - Astuty, Hendri; Winita, Rawina; Firmansyah, Nurhadi Eko; Lestiani, Budi; Zamziar, Hanny (Universitas Mohammad Husni Thamrin, 2024)
Rats (Rattus sp) are rodents that play an important role in public health as zoonoses. In the world there are 29 rodent and 171 species of the Muridae. Rats can potentially be a reservoir of infectious diseases such as from Toxocara, Capillaria hepatica and protozoan groups. Among the worms found in the intestines of rats can infect humans and animals including Echinostomes cause severe gastrointestinal, epigastric or abdominal pain accompanied by diarrhea, fatigue and malnutrition. The purpose of this study was to determine the type of rat endoparasite that has the potential to be zoonotic in the residential environment of residential of 3 villages in Bogor Regency, namely Batu City, Mekar Jaya and Parakan. This type of research is Cross-sectional approach. Sampling using random sampling technique by collecting various rat habitats as many as 100 traps. The trap success value is 11%. Rat that were caught for 3 days were 33 consisting of Rattus tanezumi (15.15%), R. norvegicus (18.2%), R.tiomanicus (12.1%), Bandicota indica (24.2%) and Mus musculus (12.1%). Microscopic results of endoparasite found hookworm eggs and larvae, Entamoeba histolytica cyst, E.coli cyst, Chilomatrix mesnili, Hymenolepis diminuta, H.nana, Trychostrongylus sp, Blastocystis hominis . The community around location should always pay attention to sanitation and maintain cleanliness to avoid the risk transmission of diseases caused rats Keyword: Endoparasite, Zoonoses, Rat